L’intégration a des limites, pas l’école inclusive ! - Thomazet, Serge (Revue des sciences de l'éducation, 2008)
In French-speaking countries, the word ‘inclusion’ tends to be used instead of integration, to refer to the schooling of pupils with special needs in regular schools. The author proposes an analysis based on the evolution of the situation in the U.S.A. to illuminate the reasons for the emergence of a new term and the advantages of adopting it. In particular, he presents an argument that, in using inclusive school, rather than describing a better-developed form of integration, we define a new paradigm that allows all pupils to find an appropriate educational setting regardless of their difficulties, and thus go beyond the limits of integration
Keywords: EHDAA; EHDAA (alumnos discapacitados o con dificultad de adaptación o de aprendizaje); besoins éducatifs; escuela inclusiva; handicap; inclusive school; integración escolar; intégration scolaire; mainstreaming; necesidades educativas; segregación; segregation; special education needs; special needs students; ségrégation; école inclusive